THE ROLE OF WOMEN VOCALISTS IN UZBEK TRADITIONAL MUSIC: A STUDY OF FEMALE CONTRIBUTIONS TO THE MAQOM ART OF UZBEKISTAN (World Bulletin of Education and Learning, 2025)
Women vocalists have played a critical, though often underrepresented, role in the evolution of Uzbek traditional music. Their contributions span musical performance, repertoire innovation, transmission of oral tradition, and preservation of regional styles within the maqom heritage. Despite historical limitations imposed by socio-cultural norms, female singers have emerged as essential figures in the shaping of Uzbek vocal aesthetics, particularly in genres such as katta ashula, folkloric songs, and, increasingly, maqom performance. This article examines the artistic, socio-cultural, and pedagogical impact of women vocalists within Uzbekistan’s maqom tradition. Drawing on ethnomusicological scholarship, archival recordings, and contemporary performance practices, the study demonstrates that women singers not only preserved regional musical identities but also expanded the expressive possibilities of maqom through unique timbral qualities, interpretative strategies, and stylistic innovations. The research seeks to reposition women vocalists as central actors in the continuity and development of Uzbek traditional music.
Keywords: Maqom; Women vocalists; Uzbek traditional music; Gender and music; Oral tradition; Performance practice; Cultural heritage; Shashmaqom; Ethnomusicology.